Private Activity in Water Supply Declined in 2008 - Izaguirre, Ada Karina; Perard, Edouard (World Bank, Washington, DC, 2012)
In 2008 nine low- or middle-income countries implemented at least 65 water projects with private participation, involving investment of more than US$3.1 billion, according to just-released data from the Private Participation in Infrastructure Project Database. The number of new projects involving the private sector declined by 20 percent compared with the peak of 2007, while annual investment commitments fell by 12 percent.